Genome-Wide Analysis of U-box E3 Ubiquitin Ligase Family in Response to ABA Treatment in Salvia miltiorrhiza - Chen, Chengan; Wang, Can; Li, Junbo; Gao, Xiankui; Huang, Qikai; Gong, Yifu; Hao, Xiaolong; Maoz, Itay; Kai, Guoyin; Zhou, Wei (Frontiers in Plant Science, 2022)
Plant U-box (PUB) proteins are ubiquitin ligases (E3) involved in multiple biological processes and in response to plant stress. However, the various aspects of the genome and the differences in functions between the U-box E3 (UBE3) ubiquitin ligases remain quite obscure in Salvia miltiorrhiza. The 60 UBE3 genes in the S. miltiorrhiza genome were recognized in the present study. The phylogenetic analysis, gene structure, motifs, promoters, and physical and chemical properties of the genes were also examined. Based on the phylogenetic relationship, the 60 UBE3 genes were categorized under six different groups. The U-box domain was highly conserved across the family of UBE3 genes. Analysis of the cis-acting element revealed that the UBE3 genes might play an important role in a variety of biological processes, including a reaction to the abscisic acid (ABA) treatment. To investigate this hypothesis, an ABA treatment was developed for the hairy roots of S. miltiorrhiza. Thirteen out of the UBE3 genes significantly increased after the ABA treatment. The co-expression network revealed that nine UBE3 genes might be associated with phenolic acids or tanshinone biosynthesis. The findings of the present study brought fresh and new understanding to the participation of the UBE3 gene family in plants, specifically in their biological responses mediated by the ABA. In S. miltiorrhiza, this gene family may be crucial during the ABA treatment. Significantly, the results of this study contribute novel information to the understanding of the ubiquitin ligase gene and its role in plant growth.